Trichosanthes cucumerina as a promising non-toxic antimalarial agent against Plasmodium berghei NK65 in animal model - Abd Jalil, Muhamad Aiman; Baba, Mohd Shukri (2019)
Malarial etiological agents were reported to be resistant against nearly all antimalarial drugs. Besides, Trichosanthes cucumerina is widely applied as vegetable in daily diets and in ethnopharmacological studies. This study was done to evaluate the antimalarial properties of aqueous extract of T. cucumerina against Plasmodium berghei NK65 and to demonstrate how this vegetable promisingly can solve a manifestation of malaria in animal model. By using the four days suppression test (4DST) method in P. berghei NK65-infected ICR male mice (25-30 g, 6-8 weeks old), the mice were intraperitoneally (i.p) infected with 0.1 mL of 1.0 x 107 parasitized red blood cells (RBC) before being orally given pre- and post-infection treatments with 0.2 mL of 100 mg/kg body weight (bw) of freeze-drying undergoes aqueous T. cucumerina extract. Microscopically, the thin blood smear showed that the mice treated with 0.2 mL of 100 mg/kg bw T. cucumerina-dH20 extract at 14 days pre-infection treatment were recorded 83.6 % of inhibition rate and 50 % of the mice in this group had survived for more than 7 months post-infection. The results for biochemical tests were positively situated in the normal ranged level. Histologically, no abnormalities and injuries were found on the selected vital organs. This study significantly evidenced that T. cucumerina could be manipulated as a potential antimalarial alternative drug for the preservation and welfare of human being.